2018
DOI: 10.1108/maj-08-2016-1425
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the voluntary use of internal audit: evidence from the UK

Abstract: Purpose This study aims to identify the factors that lead non-financial companies listed in the UK to use an internal audit function (IAF) as a monitoring mechanism. Although the use of an IAF in the UK is voluntary, no prior research has examined the drivers for using one. Design/methodology/approach Financial and non-financial data were collected from the annual reports of 332 UK non-financial companies listed on the London Stock Exchange (LSE) Main Market. Univariate tests and multivariate logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 54 publications
6
34
0
1
Order By: Relevance
“…The second stream of literature reviewed in this study is related to the internal audit function. Many studies have focused on outsourcing the internal audit function (e.g., Barr-Pulliam 2016;Abdolmohammadi 2013;Anderson et al 2012;Carey et al 2006;Ismael 2018;Davidson et al 2013;Bartlett et al 2015). For instance, Barr-Pulliam (2016) shows that approximately 38% of organizations around the world have outsourced their internal auditing functions.…”
Section: Internal Auditingmentioning
confidence: 99%
See 1 more Smart Citation
“…The second stream of literature reviewed in this study is related to the internal audit function. Many studies have focused on outsourcing the internal audit function (e.g., Barr-Pulliam 2016;Abdolmohammadi 2013;Anderson et al 2012;Carey et al 2006;Ismael 2018;Davidson et al 2013;Bartlett et al 2015). For instance, Barr-Pulliam (2016) shows that approximately 38% of organizations around the world have outsourced their internal auditing functions.…”
Section: Internal Auditingmentioning
confidence: 99%
“…Other studies on the formation of an internal audit function have focused on its determinants. Ismael (2018) investigated those factors that influence the voluntary use of internal audit. By using a sample of 332 UK non-financial companies listed on the London Stock Exchange Main Market, they found that those factors associated with the formation of an internal audit function include firm size, risks, agency problem, and effective audit committee.…”
Section: Internal Auditingmentioning
confidence: 99%
“…Both IAF and AC bond the relationship between principals and agents under the agency theory. Under the agency theory, IAF and AC are recognized as a bonding function borne by the senior managers (agent) of an organization to monitor their behaviour to ensure the interests of the shareholders (principal) of an organization are being served and protected (Ismael & Roberts, 2018). Most organizations will employ internal auditor and non-executives' directors together with the service of an AC as internal monitoring mechanisms.…”
Section: Agency Theorymentioning
confidence: 99%
“…If the relationship between the principals and the agents are utility maximisers, there is always costs incur in monitoring and bonding in order to reduce agency problem (Jensen & Meckling, 1976). The IAF is important as an internal corporate governance tool and to provide assurance on the effectiveness of the internal control and risk management control systems in order to reduce both internal and external agency costs (Ismael & Roberts, 2018).…”
Section: Moderation Role Of Iafmentioning
confidence: 99%